2022
DOI: 10.3390/antiox11020371
|View full text |Cite
|
Sign up to set email alerts
|

Yerba Mate as a Source of Elements and Bioactive Compounds with Antioxidant Activity

Elżbieta Rząsa-Duran,
Agata Kryczyk-Poprawa,
Dawid Drabicki
et al.

Abstract: Ilex paraguariensis (yerba mate) is a plant species of the holly genus Ilex native to South America from the family Aquifoliaceae and is used for the production of yerba mate infusion. The leaves of the plant are steeped in hot water to make a beverage known as mate. The present study aimed to quantify and compare the content of selected elements in dried leaves and stems of I. paraguariensis (originating from Paraguay, Argentina, and Brazil) available in the market in Poland and determine the amount of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Even though DPPH and TPC are frequently used assays for determining the antioxidant activity of tea and herbal infusions, a review of the literature showed that the results are expressed in different units, different procedures have been used, and infusions have been prepared with different methods; thus, we were unable to compare those results with those from the current study [44,45]. For example, Rz ąsa-Duran et al ( 2022) [46] assessed the antioxidant capacity of yerba mate from different origins, reporting an inhibition of the DPPH radical ranging from 20.20 to 61.29%. Regarding the polyphenolic content, the authors used different procedures to determine TPC and TFC, with results varying between 22.05 and 86.23 mg GAE/mL for TPC and between 36 and 475 mg quercetin equivalent/mL for TFC.…”
Section: Antioxidant Capacitymentioning
confidence: 82%
“…Even though DPPH and TPC are frequently used assays for determining the antioxidant activity of tea and herbal infusions, a review of the literature showed that the results are expressed in different units, different procedures have been used, and infusions have been prepared with different methods; thus, we were unable to compare those results with those from the current study [44,45]. For example, Rz ąsa-Duran et al ( 2022) [46] assessed the antioxidant capacity of yerba mate from different origins, reporting an inhibition of the DPPH radical ranging from 20.20 to 61.29%. Regarding the polyphenolic content, the authors used different procedures to determine TPC and TFC, with results varying between 22.05 and 86.23 mg GAE/mL for TPC and between 36 and 475 mg quercetin equivalent/mL for TFC.…”
Section: Antioxidant Capacitymentioning
confidence: 82%
“…Considering that the tested Yerba Mate infusions provided a large amount of polyphenolic components, known as a strong antioxidants [9,16,17,20,23], the effect of single (a) and double (b) brewing at 70 • C and 100 • C on antioxidant activity in Yerba Mate was examined in this study and the results are presented in Figure 7. The infusions obtained during the first brewing (Figure 7a) were characterized by significantly higher antioxidant activity (mean 2031.98 ± 146.47 µM TEAC/g d.m.)…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Briefly, our study confirmed previous findings reported by Boughalleb et al, [18] , Al-Saeghi et al, [28] Agour et al, [29] Sharifi-Rad et al, [30] Benchikha et al, [31] and Makhlouf-Gafsi et al [32] Generally, to assess the antioxidant potential of bioactive extracts, several factors are involved such as solvent polarity, extraction methods, plant matrix and especially phenolic compounds containing including caffeic acid, 4-feruloylquinic acid, flavonoids, alkaloids and carotenoids. [16,[33][34][35]…”
Section: Antioxidant Activitiesmentioning
confidence: 99%